The Republic of Croatia Systematic Country Diagnostic - World Bank (World Bank, Washington, DC, 2018)
Croatia has made remarkable progress since independence, but daunting challenges impede the reforms required for sustainable development. In the space of a couple of decades since independence and its subsequent destructive war, Croatia has established a liberal democracy and a market economy, and achieved upper-middle income country. EU accession played a key role in these accomplishments by supporting legislative improvements, strengthening institutions and increasing the availability of funds. Nevertheless, implementation of the reform program continues to face significant obstacles. Capture of public institutions by powerful interest groups has limited the effectiveness of reforms. And frequent changes in government, each accompanied by changes in technical staff in public administration, have reduced momentum for reform and the consistency of government policies over time. This Systematic Country Diagnostic (SCD) provides an assessment of where Croatia stands in terms of poverty reduction and shared prosperity (namely the twin goals), and how it could maximize progress towards these goals. The SCD’s purpose is not to assess the Government’s development plans but rather to articulate an independent identification of, and rationale for, priorities for achieving the twin goals. The analysis is meant to inform subsequent engagement between Croatia and the World Bank Group on the Country Partnership Framework. The document is structured as follows: chapter two presents key determinants and constraints of growth; chapter three presents determinants and constraints for enhancing inclusion; chapter four discusses financial, social and environmental sustainability, and identifies key sustainability-related constraints on achieving the twin goals over the longer term; and chapter five presents the priorities for reform and concludes.